Phenotypic characterization of Phenotypic characterization of Phenotypic characterization of Candida Candida Candida spp. isolates spp. isolates from chronic periodontitis patients from chronic periodontitis patients - Cristiane Yumi Koga-Ito; Edson Yukio Komiyama; Clélia Aparecida de Paiva Martins; Silvana Soléo Ferreira dos Santos; Ivan Balducci; Antonio Olavo Cardoso Jorge (Brazilian Journal of Oral Sciences, 2016)
Aim: Several typing methods for Candida spp. have been suggested in the literature in order to distinguish isolates for studies about the virulence or infection routes of these microorganisms and, in particular, for epidemiological purposes. The aim of this study was to establish a comparison between the phenotypic profile of oral Candida isolates from periodontitis patients and control individuals. Methods: The morphotyping and biotyping of 35 C. albicans isolates obtained from chronic periodontitis patients and 48 isolates from control individuals were performed. For morphotyping, the isolates were plated on malt extract agar and incubated for 10 days. Sixteen different morphotypes were observed for C. albicans, the most frequently observed being 0000 and 0001. Results: Biotype 0000 (complete absence of fringe) was most prevalent among the isolates obtained from periodontitis patients compared to those from control individuals, with statistical significance. Biotyping revealed 5 different biotypes with higher prevalence of the biotype 357 among the isolates from control and periodontitis groups. Conclusions: The results obtained by biotyping of the isolates did not permit to differentiate a characteristic model related to periodontal disease, whilst the morphotype 0000 was most frequently isolated from periodontitis patients.